(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Motivation serves as one of the most powerful determinants of learning effectiveness and academic performance. Within the framework of educational psychology, motivation is both a psychological drive and a pedagogical tool that determines how students engage, persist, and succeed in their studies. This paper explores the nature of motivation, its theoretical foundations, and its application in modern pedagogy. It also examines intrinsic and extrinsic motivation, the influence of self-determination, and strategies teachers can apply to enhance student motivation. Finally, it evaluates the implications of motivational theories for classroom practice and lifelong learning.